Tellurium-doped lanthanum manganite as catalysts for the oxygen reduction reaction. (9th April 2017) - Celorrio, V.; Morris, L.J.; Cattelan, M.; Fox, N.A.; Fermin, D.J.
Abstract: Abstract : The effect of tellurium (Te) doping on the electrocatalytic activity of La1− x Te x MnO3 toward the oxygen reduction reaction is investigated for the first time. La1− x Te x MnO3 with x -values up 23% were synthesized from a single ionic liquid-based precursor, yielding nanoparticles with mean diameter in the range of 40–68 nm and rhombohedral unit cell. Electrochemical studies were performed on carbon-supported particles in alkaline environment. The composition dependence activity is discussed in terms of surface density of Mn sites and changes in the effective Mn oxidation state.